Financial sector of India: emerging challenges (New Delhi, 2008)
Seventeen years of financial reforms in India have created a fairly sound framework for higher growth and integration with the world economy. Though the task is by no means complete, the groundwork that has been laid allows India to move rapidly towards the financial architecture that is appropriate for a country of India's size and aspirations. Financial markets and institutions need to evolve considerably in order to keep up with the requirements of Indian firms and Indian investors in coming years. The corporate bond market is moribund and needs to be revived. A number of missing markets will have to be created, including the exchange traded interest rate and foreign exchange derivatives contracts. But even in markets that exist, apart from the equity market for large capitalization stock, the ability to trade consistently at low cost and the tendency of market prices to reflect fundamentals are typically low for most markets. To sustain and accelerate the growth momentum, further reforms in the financial sector are called for, including a robust infrastructure for credit and an effective regulatory framework. This book contains 14 papers which examine with various dimensions of emerging financial scenario in India.
Keywords: Financial sector-India